2021
DOI: 10.1017/s0022215121001225
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of angiotensin-converting enzyme-2 in human paranasal sinus mucosa in patients with chronic rhinosinusitis

Abstract: Objective Severe acute respiratory syndrome coronavirus-2 uses angiotensin-converting enzyme-2 as a primary receptor for invasion. This study investigated angiotensin-converting enzyme-2 expression in the sinonasal mucosa of patients with chronic rhinosinusitis, as this could be linked to a susceptibility to severe acute respiratory syndrome coronavirus-2 infection. Methods Ethmoid sinus specimens were obtained from 27 patients with eosinophilic chronic rhinosinusitis, 18 with non-eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, given the lower risk for COVID-19 among CRS patients, a differential expression of ACE2 has been hypothesized. Along this line, a reduced expression of ACE2 messenger RNA (mRNA) and protein was observed in CRSwNP respiratory airway epithelial cells, including nasal polyps, 86,[89][90][91][92][93] and in olfactory mucosa 94 compared with noneosinophilic CRS and control subjects. Similar findings were reported in asthmatic patients.…”
Section: Protective Hypothesis Of Crs In Covid-19 Chronic Rhinosinusi...mentioning
confidence: 92%
“…Interestingly, given the lower risk for COVID-19 among CRS patients, a differential expression of ACE2 has been hypothesized. Along this line, a reduced expression of ACE2 messenger RNA (mRNA) and protein was observed in CRSwNP respiratory airway epithelial cells, including nasal polyps, 86,[89][90][91][92][93] and in olfactory mucosa 94 compared with noneosinophilic CRS and control subjects. Similar findings were reported in asthmatic patients.…”
Section: Protective Hypothesis Of Crs In Covid-19 Chronic Rhinosinusi...mentioning
confidence: 92%
“…H T S [25,34,35,38,39,41,[43][44][45][46][47]50,51,61]. The risk of bias (methodological quality) was assessed using the Newcastle-Ottawa scale.…”
Section: Data Organization and Risk Of Bias Assessmentmentioning
confidence: 99%
“…According to a recently published article, ACE2 expression in the sinonasal mucosa is lower in eosinophilic chronic rhinosinusitis (CRS) patients with type-2 inflammation than in patients with non-eosinophilic CRS or control subjects [ 30 ]. In addition, ACE2 regulation is positively correlated with proinflammatory cytokines such as tumor necrosis factor (TNF) and interleukin (IL)-1β in CRS patients, and negatively correlated with eotaxin-3, which chemokines related with eosinophil [ 30 ]. Another study reported that the expression of ACE2 in the sinonasal mucosa is influenced by the CRS endotypes in patients with nasal polyps.…”
Section: Reviewmentioning
confidence: 99%
“…In nasal epithelial cells, type 1 inflammation increases ACE2 expression, while type 2 inflammation decreases it [ 31 ]. Therefore, CRS type might be related to SARS-CoV-2 transmission, and an understanding of these findings might contribute to the prevention and control of COVID-19 infection [ 30 , 31 ].…”
Section: Reviewmentioning
confidence: 99%